2021
DOI: 10.1080/09638237.2021.1952955
|View full text |Cite
|
Sign up to set email alerts
|

The digital divide: factors impacting on uptake of remote therapy in a South London psychological therapy service for people with psychosis

Abstract: Background: Remote therapy promises a cost-effective way of increasing delivery of psychologicaltherapy in underserved populations. However, research shows a "digital divide", with some groups experiencing digital exclusion. Aims: To assess whether technology, accessibility, and demographic factors influence remote therapy uptake among individuals with psychosis, and whether demographic factors are associated with digital exclusion. Methods: Remote therapy uptake and demographics were assessed in people (n ¼ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
4
11
0
1
Order By: Relevance
“…It is noteworthy that some participants did not feel that the platform was confidential. Concerns regarding confidentiality and privacy reported in this study are also echoed in recent literature regarding factors influencing uptake of remote therapy in patients with psychosis (Watson et al, 2021 ). These concerns may be due to reasonable fears about the security of the internet and the video conferencing technology, and/or due to the nature of psychosis symptoms.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…It is noteworthy that some participants did not feel that the platform was confidential. Concerns regarding confidentiality and privacy reported in this study are also echoed in recent literature regarding factors influencing uptake of remote therapy in patients with psychosis (Watson et al, 2021 ). These concerns may be due to reasonable fears about the security of the internet and the video conferencing technology, and/or due to the nature of psychosis symptoms.…”
Section: Discussionmentioning
confidence: 51%
“…While a review conducted by Santesteban‐Echarri et al (2020) found limited evidence to support the notion that delusional thinking interferes with patient acceptance of telepsychiatry, recent studies indicate otherwise. For example, one study found that voices and unusual experiences or beliefs accounted for 37% of the reasons that patients with psychosis declined remote therapy during the COVID‐19 pandemic (Watson et al, 2021 ). Similarly, clinicians working with patients that experience delusional thinking also expressed concerns about using telepsychiatry with this clinical population (Cruz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that mental health is a highly relevant area in researching technology exclusion and health care engagement, as people in contact with mental health services have been found to be disproportionately affected by the “digital divide.” This is particularly marked in psychosis, with Robotham et al [ 6 ] reporting that approximately one-fifth of their sample was digitally excluded compared with only 3% of those with depression, although this rate had reduced from 30% in an earlier study [ 7 ]. Of note, excluded participants (ie, those with reduced technology access, confidence, and use) were significantly older—a finding that was replicated in a study examining factors associated with uptake of remote therapy in psychosis [ 8 ]. In a previous study by Robotham et al [ 7 ], Black people also had higher rates of exclusion, although this finding was not replicated in the follow-up study.…”
Section: Introductionmentioning
confidence: 99%
“…The varying rates are tied to socio-demographic factors, including age and economic status. Not surprisingly, older people with SMI report lower rates of smartphone ownership than younger ones ( Watson et al, 2021 ), and receipt of disability payments is a strong predictor of reduced likelihood of smartphone ownership ( Young et al, 2020 ). While there are affordable options for smartphones, the financial resources needed for purchasing data plans can be prohibitive for those living in poverty ( Vogels, n.d. ).…”
Section: Introductionmentioning
confidence: 99%